Intensification of Silviculture Techniques in Community Forest Management to Realize the Acceleration of SDG's Point 13: Handling Climate Change - Yus Andhini Bhekti Pertiwi; Muhammad Naufal Zaidan; Lelita Gian Widiya Arista; Hanifah Qothrunnada (Jurnal Indonesia Sosial Sains, 2024)
Global climate change has become an urgent issue affecting land quality, especially forest areas. Forests are important in mitigating climate change by absorbing carbon and storing greenhouse gases. Community forests, which are managed by communities on private land, have great potential to reduce carbon emissions. However, community forest management is still suboptimal due to limited knowledge of the application of effective silvicultural techniques. This study aims to provide recommendations for community forest management by intensifying silvicultural techniques, such as plant spacing and plant species selection, to reduce fire risk and support climate change mitigation. The method used was a systematic review of 30 relevant scientific articles. The literature used came from books and national and international journal articles accessed through Google Scholar, Springer and ScienceDirect databases. Articles were selected through a selection process based on the relevance of the title, abstract, and overall content. The results showed that a planting distance of 4×4 meters or 4×3 meters is the most optimal for tree growth and allows the implementation of an agroforestry system. In addition, plant species such as Swietenia macrophylla and Gliricidia sepium proved effective as fire barriers due to their evergreen characteristics that can reduce the amount of litter as fire fuel. In conclusion, intensive silvicultural techniques can increase the effectiveness of community forest management in sequestering carbon, reducing the risk of forest fires, and supporting climate change mitigation efforts. This research provides recommendations that community forest managers can apply to improve environmental sustainability.